Pemberdayaan Perempuan Dalam Pengolahan Kelapa Menjadi Virgin Coconut Oil Di Nagari Sunur, Kecamatan Nan Sabaris, Kabupaten Padang Pariaman - jusmita jusmita (Jurusan Ilmu Administrasi Negara, 2021)
Abstract This study describe the empowerment carried out to women in Nagari Sunur in processing coconut as one of the potential areas to improve community welfare and increase income. Women's empowerment is carried out by various elements, be it the local government, community institutions and the Nagari community. With the abundant coconut potential of Nagari Sunur, as well as support from various parties, it is hoped that the empowerment efforts carried out can run properly. So that people can also enjoy the results of their work. The empowerment that has been carried out has shown good results in improving the welfare of the community. However, it is undeniable that in this effort there are still obstacles that have an impact on bottlenecks in product marketing. It is hoped that the Regional Government will support this activity more so that it can motivate the community to continue producing VCO oil processed products and also so that the community is able to be creative and independent.